“PENGARUH PROSES REKRUITMEN, PROSES SELEKSI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI BAWASLU PROVINSI JAWA TENGAH” - Rijanti, Tristiana; WINDA ARISTA DEVI SAPUTRI, 15.05.51.0222 (Students' Journal of Economic and Management, 2019)
This study aims to analyze the influence of the Recruitment Process, Selection Process and Competence on Employee Performance. The object of this research is the employees of the Election Supervisory Body of Central Java Province. The population in this study were all employees in the Bawaslu in Central Java Province. The sampling technique in this study used the census method, all populations were used in the sample. The sample is 50 respondents and this study uses a method of collecting data with a questionnaire. The data collected in this study was processed using SPSS, then analyzed using correlation coefficients for testing validity, cronbach alpha for reliability testing, and multiple linear regression analysis to test the magnitude of the influence of each related variable. The model used in this study is a linear regression equation. The results of the regression analysis show that recruitment has a negative and significant effect on performance, selection has a positive and significant effect on performance, competence has a positive and significant effect on performance